SIMULATION OF DNA USING GEANT4 (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
The Geant4-DNA project entails the development of open-source software for Monte Carlo simulation-based modeling using the general-purpose toolkit Geant4. The main aim of this software is to simulate biological damage caused by ionizing radiation at cellular and subcellular levels. This project was initially initiated by the European Space Agency to forecast harmful radiation effects that may affect astronauts during future long-duration space missions. In this article, the Geant4-DNA collaboration presents an overview of the entire current project, including its latest developments already available in the latest public release of Geant4 (9.3 BETA), as well as an illustrative example of modeling direct irradiation of chromatin fiber. Expected extensions, impacting multiple scientific areas such as particle physics, chemistry, and cellular and molecular biology, within the framework of the fully interdisciplinary activity of the Geant4 collaboration, are also discussed.